Equipment investments and growth nexus – evidence from socialist and transition Croatia - Škare, Marinko; Sinković, Dean (Technological and Economic Development of Economy, 2012)
New growth theories during the 1990s stress the importance of exploring a link between investments and growth. Using standard growth equations, we look into the correlation between investment in technical structure and growth in Croatia for two periods – socialist (1960–1989) and transition (1990–2009). Results suggest that equipment investments can boost growth rates through total factor productivity (TFP). This is consistent with the work of De Long and Summers (1991, 1992, 1993, 1994) and Temple (1998). In Croatia the equipment investments – growth link appears to be stronger than the structure investment – growth link for both periods. We also find a strong positive correlation between human capital and growth. Tests confirm the consistency and robustness of the regression results, suggesting inclusion of new variables in standard growth models. The structure of technical investments, real capital stock (not proxies) and estimated human capital stock (not schooling proxies) should have an important role in explaining international growth differences.